Socio-Physical and Spiritual Environment (SPaSE) Model For Religious Moderation in Madrasa - Hanun Asrohah; Junaedi; Iskandar Ritonga (Nazhruna: Jurnal Pendidikan Islam, 2025)
This research examines the role of the Socio-Physical and Spiritual Environments (SPaSE) Model in developing religious moderation. PLS-SEM (Partial Least Square- Structural Equational Models) was used for this study to create a Social, Physical, and Spiritual Environments (SPaSE) Model for developing attitudes toward religious moderation. SEM is used in statistical techniques that measure the strength of the hypothetical relationship between variables in a model as a structure with many dependent variables. This research found that the SPaSE model represents a holistic madrasa environment with mutual relationships. In a social space, a transfer of values instills attitudes to being a good citizen. A positive social environment can promote students' social and emotional learning development to prevent intolerant behavior. Prevention may involve the physical environment, namely learning facilities, which become information about attitudes, values, and ethics in Islam compatible with a pluralistic society and prevent extremism and radicalism. The spiritual environment, as mediation and legitimacy, influences the worldview of a large group of people. This research concludes that the social, physical, and spiritual environment is significantly related to religious moderation attitudes in madrasas. The SPaSE model illustrates that students can gain specific meanings and identities through social interaction assisted by the values ​​of religious moderation. The values ​​of religious moderation that originate from Islam are the doctrines or teachings of Islam as a spiritual environment that is accustomed through social interaction and learning facilities. The SPaSE model is very important in madrasahs because it can promote attitudes and perspectives of religious moderation in madrasahs.